(untitled) (Педагогіка вищої та середньої школи, 2007)
The article deals with the achievements of the Ukrainian Shevchenkian studies of the late XIX-XX centuries in the context of the Ukrainian art studies develohment. A number of publications on Shevchenko’s work are an analyzed in the article.